2017
DOI: 10.5114/ada.2017.71117
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of Duplex Doppler ultrasound in the angiological and dermatological diagnosis of patients with blue toe syndrome

Abstract: IntroductionPeripheral microembolism is one of the most frequent causes of acute limb ischemia. In order to effectively prevent relapses it is essential to localize and eliminate the source of embolism.AimTo evaluate the role of Duplex Doppler ultrasound examination in identifying the causes of blue toe syndrome (BTS).Material and methodsThe group of 165 patients with clinical symptoms of BTS on their upper limbs (n = 16) and lower limbs (n = 149) was investigated. They all underwent Duplex Doppler ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Characteristic criteria are detection of circulating blood flow in a formation next to the artery and detection of an aneurysm neck with the typical to-and-fro flow (to-and-fro sign) [7]. For blue toe syndrome, a frequent clinical manifestation of microembolisms, ultrasound has been described as the firstchoice diagnostic procedure, enabling detection of the source of the embolism in over 90% of patients [11]. In their 2012 study dedicated to diagnosis of vascular lesions in arteries of the lower extremities, Gabriel et al [4] observed a diagnostic agreement between color duplex ultrasound and angiography in 94.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristic criteria are detection of circulating blood flow in a formation next to the artery and detection of an aneurysm neck with the typical to-and-fro flow (to-and-fro sign) [7]. For blue toe syndrome, a frequent clinical manifestation of microembolisms, ultrasound has been described as the firstchoice diagnostic procedure, enabling detection of the source of the embolism in over 90% of patients [11]. In their 2012 study dedicated to diagnosis of vascular lesions in arteries of the lower extremities, Gabriel et al [4] observed a diagnostic agreement between color duplex ultrasound and angiography in 94.6% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2345] Embolization can be spontaneous or triggered by coexistent coagulation disorders, neoplastic processes, anticoagulant/fibrinolytic therapy, and/or invasive percutaneous/endovascular procedures. [4567] If the origin of the microemboli is proximal to the bifurcation of the abdominal aorta, cutaneous involvement tends to be early and bilateral, with cyanosis and livedo reticularis affecting several digits. According to the site of origin, emboli may also affect other body regions, such as kidneys, liver, spleen, pancreas, gastrointestinal tract, and adrenal glands, with mortality as high as 81% in cases of multiple organ involvement.…”
mentioning
confidence: 99%
“…Complete past medical history, physical examination, basic laboratory tests, and noninvasive vascular assessment must be carefully evaluated by dermatologists, since early cutaneous findings can play a fundamental role in initiating the correct BTS management. [7] However, a multidisciplinary approach is required to suggest the optimal medical or surgical therapeutic strategy.…”
mentioning
confidence: 99%